2021
DOI: 10.1111/1440-1681.13525
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine attenuates one‐lung ventilation associated lung injury by suppressing inflammatory responses: A systematic review and meta‐analysis

Abstract: One‐lung ventilation (OLV), a common ventilation technique, is associated with perioperative lung injury, tightly connected with inflammatory responses. Dexmedetomidine has shown positive anti‐inflammatory effects in lung tissues in pre‐clinical models. This study investigated the efficacy of dexmedetomidine for suppressing inflammatory responses in patients requiring OLV. We searched PubMed, MEDLINE, Embase, Scopus, Ovid, and Cochrane Library for randomized controlled trials focusing on dexmedetomidine’s anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 43 publications
3
11
0
Order By: Relevance
“…Perioperative application of DEX can reduce the inflammatory response caused by OLV and improve pulmonary oxygenation, which may help reduce the postoperative complications. 31 Taken together, these findings suggested a reduction in postoperative pulmonary complications in lung cancer patients treated with DEX.…”
Section: Discussionmentioning
confidence: 76%
“…Perioperative application of DEX can reduce the inflammatory response caused by OLV and improve pulmonary oxygenation, which may help reduce the postoperative complications. 31 Taken together, these findings suggested a reduction in postoperative pulmonary complications in lung cancer patients treated with DEX.…”
Section: Discussionmentioning
confidence: 76%
“…In recent years, evidence has emerged that DEX, a widely used anesthesia adjunct, exhibits numerous anti-inflammatory mechanisms with researches reporting benefits in multiple organ protection [ 30 , 31 ]. For example, DEX has been verified with potent protections in several cases of lung injury, such as ventilation-associated lung injury [ 24 ], ischemia/reperfusion injury [ 22 ], and endotoxin-induced acute injury [ 23 , 32 ]. In addition, our previous study has demonstrated that DEX was capable to attenuate airway inflammation in an ovalbumin-induced asthma model [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…A longitudinal midline incision was made to the neck to expose the trachea, and the trachea was cannulated and connected to the Flexivent system to ventilate at 160 breaths/min, 200 μl tidal. After the baseline of respiratory mechanics was recorded, mice were challenged with increasing doses of aerosolized methacholine (6,12,24, and 48 μg/g). Total respiratory resistance (Rrs) was recorded to assess the airway hyperresponsiveness.…”
Section: Measurement Of Lung Function and Methacholinementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, dexmedetomidine reduces the inflammatory response during 1-lung ventilation, thereby reducing lung injury; this effect may be associated with improved intrapulmonary shunting in patients. [ 19 , 20 ]…”
Section: Discussionmentioning
confidence: 99%